ANALISIS BIBLIOMETRIK : GREEN FINANCE - Bela Septiana; Nur Rahmad Alfin Mustaqim; Siti Mujanah; Achmad Yanu Alif Fianto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
Green Finance has emerged as a crucial pillar in global efforts to achieve environmental sustainability and climate change mitigation. This concept encompasses financial practices that support investments in projects with positive environmental impacts, such as renewable energy and sustainable resource management. This study aims to conduct a bibliometric analysis of the Green Finance literature to understand its developments and trends in the field. The bibliometric analysis method is employed by collecting data from Google Scholar, targeting 500 journals published between 2014 and 2024. The results indicate significant growth in publications related to Green Finance, with thematic mapping identifying five main clusters including climate change, green technology, and other practical applications. In conclusion, this research recommends several themes for further investigation, such as the influence of Green Finance on green products and financial performance. Ongoing research is expected to significantly contribute to the development of more sustainable financial practices